HUBUNGAN TERPAAN MEDIA SOSIAL APLIKASI RUANGGURU TERHADAP MOTIVASI BELAJAR SISWA KELAS VI DI SD NEGERI 2 TAHUNAN - Della Putri, Kiki Shalsa; Sekar Wangi, Maya; Maserona Sarungu, Lukas (Solidaritas, 2025)
ABSTRACT This research aims to analyze the relationship between the impact of social media from the Ruangguru application and the learning motivation of sixth-grade students at SD Negeri 2 Tahunan. This study employs new media theory in examining the relationship between the impact of social media from the Ruangguru application and the learning motivation of sixth-grade students at SD Negeri 2 Tahunan. The type of research conducted is quantitative research, where data collection is carried out using questionnaires. The population and sample in this study consist of 30 sixth-grade students (respondents) from SD Negeri 2 Tahunan. The analysis technique used is Spearman's correlation. The results indicate that the variable of the impact of social media from the Ruangguru application has a significant simultaneous effect on the learning motivation of sixth-grade students at SD Negeri 2 Tahunan. The variable of the impact of social media from the Ruangguru application also has a significant partial effect on the learning motivation of sixth-grade students. The calculated t value is 4.310 with a p-value of 0.001<0.05, thus H1 is accepted. This indicates that there is a relationship provided by the Ruangguru Application (X) towards the dependent variable (Y) in sixth-grade students of SD Negeri 2 Tahunan. Keywords: Media exposure, Application, Ruangguru, learning motivation.